2007
DOI: 10.1016/s1130-1473(07)70295-6
|View full text |Cite
|
Sign up to set email alerts
|

Late prevertebral abscess following anterior cervical plating: The missing screw

Abstract: A 51-year-old man underwent a C5-C7 anterior decompression and fusion. Six years later the patient complained of dysphagia caused by displacement of the cervical plate. One week after the scheduled removal of the implanted material, the patient developed a painful cervical swelling and fever. His cervical radiographs showed that a screw was missing compared to previous studies. Computerized tomography showed a large prevertebral abscess anterior to C4-C7. He underwent emergency surgical drainage of the abscess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…17 However, anterior cervical plates and screws are associated with both immediate and delayed hardware complications such as screw or plate migration and breakage. 6,26,32,39,43 Despite improvements in anterior cervical instrumentation, such as improved screw-locking mechanisms, complications persist. 14,15,25 Moreover, anterior cervical instrumentation is believed to contribute to the chronic postoperative dysphagia that can occur after ACDF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, anterior cervical plates and screws are associated with both immediate and delayed hardware complications such as screw or plate migration and breakage. 6,26,32,39,43 Despite improvements in anterior cervical instrumentation, such as improved screw-locking mechanisms, complications persist. 14,15,25 Moreover, anterior cervical instrumentation is believed to contribute to the chronic postoperative dysphagia that can occur after ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…An anterior plate is commonly added to enhance construct stability and reduce the rate of pseudarthrosis; however, this addition may be complicated by postoperative dysphagia, softtissue injury, and hardware failure. 2,[4][5][6]19,26,32,34,39 The pathophysiological mechanism of postoperative dysphagia remains unknown, but proposed causes include soft-tissue edema, postoperative hematoma, recurrent laryngeal nerve palsy, esophageal injury, postoperative adhesions, and device migration. 15 Some studies suggest patient age, sex, body mass index (BMI), blood loss, location of surgery, and number of operated levels as possible contributing factors to dysphagia.…”
mentioning
confidence: 99%
“…Six years after surgery, the patient presented with dysphasia, and in the radiological examination, the screw could no longer be identified. Plate and screw systems were removed, and the patient was treated for prevertebral abscess secondary to esophagus perforation [8]. Gazzeri et al reported a case of spontaneous healing of esophagus fistule due to screw elimination through the intestinal tract one week after the patient complained of dysphasia and high fever [17].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, these materials may penetrate into esophagus and eliminate through the intestinal tract [3,[5][6][7][8]. In this study, we report a late complication of displacement and loss of an anterior cervical plate and screws in an asymptomatic patient.…”
Section: Introductionmentioning
confidence: 91%
“…glossopharyngeal nerve, hypoglossal nerve, recurrent laryngeal nerve and vagus nerve) due to surgical manipulation with prevertebral soft tissue swelling and postoperative fibrosis causes decreased pharyngeal wall movement, incomplete epiglottic deflection, impaired upper esophageal sphincter opening with adhesion formations at the vallecular and pyriform sinuses (1-3). If dyspagia is seen at the early postoperative period, fever may or may not accompany this symptom, prevertebral abscess should be considered (4). Perforation also can be ocur associated with an vertebral osteomyelitis (5).…”
mentioning
confidence: 99%